Fiction deliberation as functional and semantic type of creative writing in a foreign language - Tozik, Oksana V. (Journal of the Belarusian State University. Philology, 2019)
The prospects of the fiction deliberation teaching as functional and semantic type of creative writing in a foreign language during professional philologists’ training are grounded. The author analyzes the correlation between fiction deliberation acquisition during the analysis of general fiction works and personal fulfilment, self-development connected with students’ creativity that encourages deeper and more comprehensive learning and a thorough insight into the works’ implied meanings. Integrating function of the fiction deliberation is proved by the revealed meaningful communicative and functional, logical and semantic, structural and compositional peculiarities of functional and semantic type of creative writing in a foreign language during the students’ independent work, which is currently considered as the main component of higher education in higher educational establishments.